Association of Metabolic Syndrome and Inflammation with Cognitive Decline in Adults Aged 60 Years and Older: Findings from a National Health Survey in the United States. (26th December 2013) - Liu, Zuolu; Lippa, Carol F.
Abstract : Objectives . We aimed to test the hypothesis that metabolic syndrome (MetS) is significantly associated with cognitive decline (CoD) in elderly adults and further assess whether MetS and inflammation have a significant joint effect on CoD. Methods . Data (n = 2975 ) from the U.S. National Health and Nutrition Examination Survey (1999–2002) in participants aged ≥60 years who had Digit Symbol Substitution Tests (DSS: a standard measure of cognitive function) were studied. CoD was defined as those in the lowest quintile of DSS score. MetS was defined as having ≥3 of 5 MetS traits (large waist circumference (WC), high blood pressure (BP), elevated glucose, triglycerides, and decreased high density lipoprotein cholesterol). Results . Of 2975 participants, the prevalence of CoD (DSS score <25) was 12.1%. After adjusting covariates, individual large WC, high BP, elevated glucose level, and MetS were significantly associated with CoD in logistic regression models (P < 0.001 ). There was a significant dose-response relationship between an increased number of MetS traits and CoD (P < 0.001 ). A significant joint effect of MetS and CRP on the odds of CoD was observed. Conclusion . The study, using a nationally representative sample, extended previous studies by highlighting a significant MetS-CoD relationship and a joint effect of MetS and CRP on CoD. These novel findings add to our understanding of the association of neurometabolic disorders and cognition and have implications that may be relevant to primary care practice.